Linking resting state metabolite concentrations in the dorsal anterior cingulate cortex to response inhibition in OCD, a combined fMRI-MRS study - Niels T. de Joode; Anders L. Thorsen; Chris Vriend; Petra J.W. Pouwels; Anton J.L.M. van Balkom; Kristen Hagen; Olga T. Ousdal; Bjarne Hansen; Gerd Kvale; Odile A. van den Heuvel (Journal of Affective Disorders Reports, 2023)
Introduction: Obsessive-compulsive disorder (OCD) has been associated with abnormal brain activation in regions related to response inhibition, such as the dorsal anterior cingulate cortex (dACC), as well as dysregulation of the glutamate system. We studied how the neurometabolites glutamate and glutamine (Glx) in the dACC are related to task performance and task-related brain activation during a response inhibition task in OCD patients and healthy controls (HC). Methods: We combined resting-state magnetic resonance spectroscopy (1H-MRS) in the dACC and functional MRI (fMRI) during the Stop Signal Task (SST), using data from two sites (43 OCD patients and 41 HC). For fMRI data, region of interest (ROI) and whole brain analyses were performed during successful inhibition and error processing. Subsequently, the relation between baseline Glx concentrations, task-related activation, functional connectivity, and task performance was tested using correlational analyses. Results: In HC, Glx concentration in dACC showed a positive correlation with inhibition-related activation in the right thalamus (based on ROI analyses) and the brain stem (based on whole brain analyses). No relation between Glx and task-related activation was observed in patients with OCD. SST performance was not different between groups and was not associated with dACC Glx concentrations. Limitations: Although we attempted to link neurometabolite levels and brain activation, the non-simultaneous acquisition of 1H-MRS with fMRI made it difficult to interpret the results. Conclusions: We conclude that dACC Glx is associated with inhibition-related activation and network function in HC, but not in OCD, suggesting altered inhibition processing in OCD.